Regolith-based additive manufacturing for sustainable development of lunar infrastructure – An overview. (March 2021) - Isachenkov, Maxim; Chugunov, Svyatoslav; Akhatov, Iskander; Shishkovsky, Igor
Abstract: This review discusses the development prospects of additive technologies for the manufacturing of complex technological items on the surface of the Moon under scarce resource availability and low-gravity conditions. One of the expected materials for 3D printing as part of a prospective lunar research program is the lunar regolith. It is easily accessible on the Moon in a few forms, depending on geographical location. Due to the limited availability of the lunar regolith on Earth, several attempts to use geological simulants of the regolith were made by research groups worldwide to analyze the applicability of additive manufacturing (AM) technologies for lunar 3D printing. The present review is aimed at discussing recent achievements in the development of chemical and technological aspects of 3D-printing technology for the use of the lunar regolith. A detailed description of all known AM approaches is presented, and the results obtained by various research groups are compared and discussed. All available experiments with 3D printing for in-situ fabrication with lunar regolith were analyzed, systematized, and generalized. Finally, we have formulated the basic requirements and approaches for adapting additive manufacturing methods to lunar surface conditions. Highlights: Systematization of all cases of additive manufacturing with lunar regolith. Comparison of different additive manufacturing approaches. Evaluation of in-situ fabrication and repair techniques. Importance of pre- and post-treatment for manufacturing lunar regolith . Recommendations on the additive manufacturing for lunar exploration.